2011
DOI: 10.1103/physrevlett.106.047001
|View full text |Cite
|
Sign up to set email alerts
|

Phase Fluctuations in a Strongly Disordereds-Wave NbN Superconductor Close to the Metal-Insulator Transition

Abstract: We explore the role of phase fluctuations in a three-dimensional s-wave superconductor, NbN, as we approach the critical disorder for destruction of the superconducting state. Close to critical disorder, we observe a finite gap in the electronic spectrum which persists at temperatures well above T(c). The superfluid density is strongly suppressed at low temperatures and evolves towards a linear-T variation at higher temperatures. These observations provide strong evidence that phase fluctuations play a central… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
194
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(233 citation statements)
references
References 36 publications
38
194
1
Order By: Relevance
“…14 Moreover, the observation of a pseudogap in strongly disordered SC films [8][9][10][11][12][13] bears some resemblance to similar experimental findings in high-temperature superconductors [15][16][17] that may suggest a common mechanism in some regions of the phase diagram.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…14 Moreover, the observation of a pseudogap in strongly disordered SC films [8][9][10][11][12][13] bears some resemblance to similar experimental findings in high-temperature superconductors [15][16][17] that may suggest a common mechanism in some regions of the phase diagram.…”
Section: Introductionmentioning
confidence: 64%
“…For a given disorder strength only few sites are close to this regime and their number decreases with increasing V 0 /t due to the decrease of SC islands. There are also few sites, as (10,5), where the SC order parameter reemerges at a large value of the disorder strength and stays finite over some range of V 0 . In the appendix the behavior of ∆ i and χ AA ii for all sites of the sample is analyzed in more detail.…”
Section: Real Space Structure Of Responsesmentioning
confidence: 99%
“…Early work focused on the most easily measurable quantity, the DC conductivity. [1-3, 6-10] Recently, due to the availability of local scanning probes, attention has turned to the tunneling behavior [11][12][13][14][15]. In the case of the disorder-tuned SIT [15], it has become clear that the SIT is ultimately due to a bosonic mechanism [16] rather than a fermionic one [17].…”
mentioning
confidence: 99%
“…1, indicating a similar energy gap but, importantly, almost no coherence peaks at the gap edges are present. This reminds the evolution of spectra found in strongly disordered InO [2] and NbN [3]. Moreover, a reduced tunnelling conductance around the zero bias is found here also for temperatures above the resistive T c = 3.8 K. The dotted and dashed curves in Fig.…”
Section: Resultsmentioning
confidence: 52%
“…A question has been raised if at the transition the Cooper pairs become localized, or rst the superconductivity is suppressed and then the standard localisation of single electrons leads to insulating state. Recent tunnelling experiments on homogenously disordered superconducting lms [2,3] accumulated a support for the rst hypothesis. It has been shown that in highly disordered lms the coherence peaks in the superconducting density of states disappear close to SIT but superconducting gap can be found even above the resistive transition temperatures T c , reminding the pseudo-gap in high-T c cuprates.…”
Section: Introductionmentioning
confidence: 93%